2011
DOI: 10.4054/mpidr-wp-2011-010
|View full text |Cite
|
Sign up to set email alerts
|

Economic conditions of stepfamilies from a cross-national perspective

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily refl ect those of the Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…unions where at least one child originated from a prior partnership. Research on "stepfamily fertility" has revealed that the family size of stepfamilies tends to be larger than that of families with only common children (Kreyenfeld and Martin 2011;Martin 2008;Mignot 2008). This pattern is attributed to "union commitment" whereby couples want to cement their relationship with a common child, so that partners in a stepfamily are more likely to progress to births of higher order than partners with only common children (Henz and Thomson 2005;Holland and Thomson 2011;Thomson 2004;Vikat et al 1999).…”
Section: Prior Findingsmentioning
confidence: 99%
“…unions where at least one child originated from a prior partnership. Research on "stepfamily fertility" has revealed that the family size of stepfamilies tends to be larger than that of families with only common children (Kreyenfeld and Martin 2011;Martin 2008;Mignot 2008). This pattern is attributed to "union commitment" whereby couples want to cement their relationship with a common child, so that partners in a stepfamily are more likely to progress to births of higher order than partners with only common children (Henz and Thomson 2005;Holland and Thomson 2011;Thomson 2004;Vikat et al 1999).…”
Section: Prior Findingsmentioning
confidence: 99%
“…While these differences are to be kept into account in making cross-national comparisons, studies have shown that both American and European families are subject to the nuclear family ideology (Ganong & Coleman, 2016 ) and are largely influenced by the same myths, beliefs, and stigmatization (Kreyenfeld & Heintz-Martin, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, trying to assess and treat stepfamily problems using traditional family therapy approaches often leads to client dropout (Ford & Hecker, 2008 ; Pasley, Rhoden, Visher, & Visher, 1996 ) and dissatisfaction with treatment (Higginbotham & Adler-Baeder, 2008 ). Despite the increasing number of stepfamilies in all Western countries (Furnkranz- Prskawetz et al, 2003 ; Kreyenfeld & Heintz-Martin, 2011 ), few publications address the specific issues and techniques to be used in stepfamily therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this decline, the economic disparities between children from two‐parent families and single‐parent families remained smaller in East Germany (Joos, ; Walper, ). Moreover, in West Germany—but not in East Germany—stepfamilies also fare economically worse than traditional nuclear families (Kreyenfeld & Martin, ). Thus, as far as the effect of family structure is mediated by economic hardship and status transmission, its impact on early family formation should be weaker in East Germany for both study cohorts although the East–West differences might be smaller for the younger study cohort due to socioeconomic change caused by the unification, that is, less support for single mothers and lower child‐care coverage.…”
Section: Introductionmentioning
confidence: 99%